Profound Intraoperative Metabolic Acidosis and Hypotension in a Child Undergoing Multilevel Spinal Fusion - Mohanad Shukry; Jonathan A. D'Angelo; Minal Joshi; Jorge A. Cure; Alberto J. de Armendi (Case Reports in Medicine)
The prone position may cause cardiovascular system depression. Yet, the mechanisms involved and preemptive measures are not well understood (Edgcombe et al. (2008)). During spinal surgery in the prone position, hypotension may occur. Implicated factors include prolonged abdominal compression impeding venous return resulting in increased blood loss, decreased cardiovascular reserve, and the use of total intravenous anesthesia (TIVA) which has been shown to blunt the sympathetic response more than inhalation anesthesia. We present a case of hypotension during spinal surgery with all its challenges. Hypotension and acidosis persisted despite all supporting measures, and only to improve with supine positioning. Differential diagnosis for such an event are discussed. Although abdominal compression may not be obvious before the start of surgery, compressing the spine during surgery may lead to abdominal compression and hypoperfusion to abdominal organs.